Single‐incision multiport laparoendoscopic surgery using a short‐type flexible endoscope and its usefulness in cholecystectomy. Issue 1 (11th November 2014) - Yamaguchi, Takashi; Abe, Nobutsugu; Matsunobu, Shuuichiro; Mizuno, Hideaki; Yanagida, Osamu; Takeuchi, Hirohisa; Masaki, Tadahiko; Mori, Toshiyuki; Sugiyama, Masanori
Abstract Introduction We previously demonstrated the advantages of a short‐type flexible endoscope as a working scope in laparoscopic surgery through single‐incision procedures in animal experiments. In this report, we examined the outcomes of laparoscopic surgery through a single incision using a flexible endoscope in a clinical setting. Specifically, we performed cholecystectomy using single‐incision multiport laparoendoscopic (SIMPLE) surgery. Methods Thirteen patients with cholecystolithiasis or gallbladder polyp underwent SIMPLE cholecystectomy using a newly developed short‐type flexible endoscope with a working length of 60 cm. Twenty‐seven patients underwent standard single‐incision laparoscopic cholecystectomy using a 5‐mm rigid laparoscope. We retrospectively compared the surgical outcomes between the two groups. Results SIMPLE cholecystectomy using the short‐type flexible endoscope was successfully carried out. No gallbladder perforation occurred, but perforation occurred in four cases in the standard laparoscopic cholecystectomy group; however, the difference was not statistically significant. Although no other surgical outcomes differed between the two groups, the flexible endoscope had several advantages over the standard laparoscope. The scope provided a flexible view of the operating field. The gallbladder dissection using the cutting device via the scope was easier and safer than that in standard single‐incision laparoscopic cholecystectomy. The water‐jet, suctioning, and self‐cleaning lens functions of the scope served the surgery well. Conclusions SIMPLE cholecystectomy using a short‐type flexible endoscope has surgical outcomes equivalent to those of standard single‐incision laparoscopic cholecystectomy, but this endoscope with multiple functions may make the surgical procedures less stressful and safer.